Peran Public Relations Dalam Membangun Citra Positif Produk Sunscreen The Originote - Susan Ary Ayu Anjani; Shela Amelia Akhap; Dian Islami; Tria Patrianti (STIKes Ibnu Sina Ajibarang, 2024)
The Originote provides skincare and beauty products. Starting from moisturizers to sunscreens, The Originote launched several skincare products that caught the public's attention. Until the brand name The Originote became viral on social media because many users felt helped by The Originote products, one of which was sunscreen. A viral video circulating on TikTok social media shows the LAB test results of a sunscreen whose SPF does not match those on the product packaging. The video was made by TikTok content creator @cicikoko_review. However, the video does not tell what brand of sunscreen the SPF does not match. This is what makes netizens and users of The Originote sunscreen products worried and suspect that The Originote is one of those included in sunscreen that has fake SPF. This research aims to find out how the role of Public Relations in building a positive image of The Originote products. In addition, this study will also identify factors that influence public perception after the occurrence of overclaim cases in The Originote sunscreen products. This research uses a literature study method with a qualitative approach. To validate the data, cross-reference analysis was conducted, comparing findings from various sources that were verified for reliability.